2015
DOI: 10.4028/www.scientific.net/aef.13.83
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory NiTi and NiTiCu Alloys Obtained by Spark Plasma Sintering Process

Abstract: Abstract. The addition of Cu to near equiatomic NiTi shape memory alloys (SMAs) can provide some modifications of their shape memory properties by affecting their transformation behavior. The same effect was obtained in the case of Ni 3 Ti 2 and Ni 4 Ti 3 precipitates presence in the microstructure of NiTi. Also the substitution of Cu to NiTi alloys increases the hardness of the materials. This paper presents the microstructural and mechanical investigations of NiTi and NiTiCu alloys obtained by spark plasma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The investigated NiTiCu samples with the compositions Ni 45 Ti 50 Cu 5 and Ni 40 Ti 50 Cu 10 (at.%) were made at INCDIE ICPE-CA in previous studies [ 3 , 6 ] by powder technology with and without MA up to 15 h. The samples were made from Ni (with 10 µm particle size), Ti (with 150 µm particle size) and Cu (with <63 µm particle size) elemental powders, acquired from Merck, Darmstadt, Germany. Four samples with different processing and alloying methods are compared: without MA and with 5 at.% Cu alloyed (Ni 45 Ti 50 Cu 5 with notation HT-P0), without MA and with 10 at.% Cu (Ni 40 Ti 50 Cu 10 with notation HT-S0), with MA and with 5 at.% Cu alloyed (Ni 45 Ti 50 Cu 5 with notation HS-P1), and with MA and with 10 at.% Cu alloyed (Ni 40 Ti 50 Cu 10 with notation HS-S1).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The investigated NiTiCu samples with the compositions Ni 45 Ti 50 Cu 5 and Ni 40 Ti 50 Cu 10 (at.%) were made at INCDIE ICPE-CA in previous studies [ 3 , 6 ] by powder technology with and without MA up to 15 h. The samples were made from Ni (with 10 µm particle size), Ti (with 150 µm particle size) and Cu (with <63 µm particle size) elemental powders, acquired from Merck, Darmstadt, Germany. Four samples with different processing and alloying methods are compared: without MA and with 5 at.% Cu alloyed (Ni 45 Ti 50 Cu 5 with notation HT-P0), without MA and with 10 at.% Cu (Ni 40 Ti 50 Cu 10 with notation HT-S0), with MA and with 5 at.% Cu alloyed (Ni 45 Ti 50 Cu 5 with notation HS-P1), and with MA and with 10 at.% Cu alloyed (Ni 40 Ti 50 Cu 10 with notation HS-S1).…”
Section: Methodsmentioning
confidence: 99%
“…The EDX and XRD showed the presence of the minority austenite phase and martensite as the majority phase. Moreover, they have confirmed that Ni 2 Ti/(Ni, Cu) 2 Ti, NiTi 2 /(Ni, Cu)Ti 2 and Ni 3 Ti/(Ni, Cu) 3 Ti phases exist, that the samples were properly compacted and the density calculated by Archimedes' method was 5.041 ÷ 6.664 g/cm 3 [6]. The densification of NiTiCu materials is higher in the high-Cu samples' content.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations